Articulatory and acoustic inter-speaker variability in the production of German vowels - Weirich, Melanie (ZAS Papers in Linguistics, 2010)
This study examines articulatory and acoustic inter-speaker variability in the production of the German vowels /i/, /u/ and /a/. Our subjects are 3 monozygotic twin pairs (2 female and 1 male pair) and 2 dizygotic female twin pairs. All of them were born, raised and are still living in Berlin and see their twin brother or sister regularly. We assume that monozygotic twins that are genetically identical and share the same physiology should be more similar in their articulation than dizygotic twins but that the shared time and social environment of twins, regardless of their genetic similarity, also plays a crucial role in the acoustic similarity of twins. Articulatory measurements were made with EMA (Electromagnetic Articulography) and the target positions of the produced vowels were analyzed. Additionally, the formants F1-F4 of each vowel were measured and compared within the twin pairs. Our data seems to point out the importance of a shared environment and the strong influence of learning over the anatomical identity of the monozygotic twins regarding the production of vowels. But, additional results suggest (1) the impact of physiology on the production of a vowel following a velar consonant and (2) the interaction of physiology and stress in inter-speaker variability.